2008
DOI: 10.1523/jneurosci.3568-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Activation of Microglia Is Promoted by a Nox1-Dependent NADPH Oxidase

Abstract: Reactive oxygen species (ROS) modulate intracellular signaling but are also responsible for neuronal damage in pathological states. Microglia, the resident CNS macrophages, are prominent sources of ROS through expression of the phagocyte oxidase which catalytic subunit Nox2 generates superoxide ion (O 2 ⅐Ϫ ). Here we show that microglia also express Nox1 and other components of nonphagocyte NADPH oxidases, including p22 phox , NOXO1, NOXA1, and Rac1/2. The subcellular distribution and functions of Nox1 were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
177
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(185 citation statements)
references
References 73 publications
(95 reference statements)
8
177
0
Order By: Relevance
“…Activation of IFN-γ receptors triggers various responses in macrophages and microglia (37,51). Moreover, there is cross-talk between TLR4 and the IFN-γ receptor via autocrine and paracrine loops at various intracellular downstream cascades (37,52). The promoter of iNOS gene (Inos) is operated by both STAT1 and NFκΒ transcription factors, activated by IFN-γ receptor and TLR4, respectively (37,53); thus, coincident STAT1/NFκB signaling up-regulates iNOS transcription and subsequent NO release to the critical neurotoxic level (11,32,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of IFN-γ receptors triggers various responses in macrophages and microglia (37,51). Moreover, there is cross-talk between TLR4 and the IFN-γ receptor via autocrine and paracrine loops at various intracellular downstream cascades (37,52). The promoter of iNOS gene (Inos) is operated by both STAT1 and NFκΒ transcription factors, activated by IFN-γ receptor and TLR4, respectively (37,53); thus, coincident STAT1/NFκB signaling up-regulates iNOS transcription and subsequent NO release to the critical neurotoxic level (11,32,34).…”
Section: Discussionmentioning
confidence: 99%
“…The promoter of iNOS gene (Inos) is operated by both STAT1 and NFκΒ transcription factors, activated by IFN-γ receptor and TLR4, respectively (37,53); thus, coincident STAT1/NFκB signaling up-regulates iNOS transcription and subsequent NO release to the critical neurotoxic level (11,32,34). TLR4 and/or IFN-γ receptor activation also up-regulate NADPH oxidase, which generates superoxide anions (20,52). Superoxide anions can rapidly oxidize NO, resulting in highly toxic peroxynitrite (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative forms include NOX1, NOX3, NOX4, NOX5, DUOX1, and DUOX2, and differ in their requirements for cytosolic and membrane subunits. In addition to NOX2, microglia have been shown to express functional NOX1 [12] and NOX4 [13]. Furthermore, NOX1, NOX2, and NOX4 are expressed in neurons, astrocytes, endothelial cells, pericytes and fibroblasts, among other cells [14,15].…”
Section: Nadph Oxidasementioning
confidence: 99%
“…Ex vivo EPR studies on aortic rings also showed absence of an O 2 •-signal in response to AngII in EBP50 KO, correlating with findings in Nox1 KO. Moreover, in vivo data demonstrated that in response to another robust inducer of Nox-derived ROS, LPS (27)(28)(29)(30)(31)(32)(33), vascular medial smooth muscle oxidation was absent in EBP50 KO mice. Because Nox1 is a major source of O 2…”
Section: Discussionmentioning
confidence: 98%